Enhancing Grade 4 Students’ Area and Volume Understanding and Mathematical Creative Thinking through Project-Based Learning: A Systematic Literature Review - Amriah, Amriah; Supriadi, Supriadi; Sutarsih, Cicih (Journal of Innovation and Research in Primary Education, 2025)
Grade 4 elementary school students often face difficulties in understanding mathematical concepts such as area and volume, which require connecting abstract reasoning with concrete representations. At the same time, creative thinking is increasingly recognized as an essential 21st-century skill that supports problem-solving and innovation. Project-Based Learning (PjBL) has been widely recommended to address these challenges; however, a systematic synthesis of its effectiveness in elementary mathematics, particularly on area and volume learning and creative thinking, remains limited. This study conducted a systematic literature review of empirical research published between 2018 and 2024. Following PRISMA 2020 procedures, five databases (Scopus, ERIC, Garuda, DOAJ, and SINTA) were searched. From 1,111 records initially identified, 743 were screened, 572 assessed for eligibility, and 50 experimental or quasi-experimental studies were included. Data were analyzed through meta-analysis and thematic coding to capture both quantitative effect sizes and qualitative insights. The results show that PjBL yields a substantial positive impact, with an overall effect size of d = 0.78 (95% CI: 0.65–0.91) for students’ understanding of area and volume, and d = 0.74 (95% CI: 0.60–0.88) for creative thinking skills. Projects lasting three to four weeks and integrating cultural contexts, such as Meru-Bali architecture, resulted in the highest mastery levels (85–100%). Improvements were also observed across the creativity dimensions of fluency, flexibility, originality, and elaboration (n-gain 0.47–0.86). Moderating factors include teacher scaffolding, STEM/STEAM integration, and student autonomy. Overall, PjBL demonstrates substantial potential for strengthening area and volume comprehension while fostering creative thinking in Grade 4 mathematics. The findings provide evidence-based design principles for implementing context-based PjBL and practical guidance for curriculum developers and teacher training programs.